The Diversity of Food Consumption, Physical Activity and Nutritional Status of Menopause Women - Tina Rahmawati; Emma S Wirakusumah; Budi Setiawan (Media Gizi dan Keluarga, 2001)
The objectives of this research were to know the influence of educational level, nutritional knowledge and food expenditure to the diversity of food consumption; the influence of diversity in food consumption to the adequacy level of nutrients; the influence of the adequacy level of energy and physical activity to nutritional status; and also pre menopause symptoms and post menopause illness. The research showed that educational level has a positive significant influence on food consumption diversity. However, nutritional knowledge and food expenditure, so far, have no significant influence. The diversity of food consumption has a positive significant influence on the adequacy level of nutrients. The adequacy level of energy, has no significant influence on nutritional statu. However, physical activity positively influences the nutritional status. Pre menopause symptom reported by most of the samples is painful symptom and the post menopause illness is rheumatism